Roles of model size and particle size distribution on macro-mechanical properties of Lac du Bonnet granite using flat-joint model. (November 2018) - Li, Kaihui; Cheng, Yungming; Fan, Xiang
Abstract: In this study, a new calibration procedure was proposed to calibrate the micro-parameters for the flat-joint model. Both uniaxial compression and Brazilian test simulations were conducted on standard and same-porosity specimens using flat-joint model. With increasing model size, the uniaxial compression strength (UCS), crack-initiation stress, Young's modulus and Poisson's ratio decrease initially until achieving stable values, while the Brazilian tensile strength (BTS) follows the descending trend and UCS/BTS maintains increasing with increasing model size. It is found that BTS is best fitted by the fracture energy and multifractal size-effect models for which the fitting constants are functions of the grain size heterogeneity ( d max / d min ). All the macro-properties are found to decrease with increasing d max / d min . It is also demonstrated that the constitutive contact model affects the effects of model size and particle size distribution.